Design and dSPACE Implementation of a Simplified Fuzzy Control of a DC-DC Three-Level Converter - Hajar Doubabi; Issam Salhi (Journal of Electrical and Computer Engineering)
The design of an efficient DC-DC converter depends critically on its suitable control. In this paper, a new simplified output tracking control strategy for a DC-DC three-level boost converter is presented. The proposed strategy is characterized by its good tracking performances, its simplicity of design, and the stability that is ensured over the entire operating range. Thanks to (i) the adopted Takagi–Sugeno (TS) fuzzy approach; (ii) the small-signal model derived under the large domain of operating conditions, and (iii) the proportional-integral (PI) controllers’ merit. After introducing the three-level boost converter topology, the operating principles and mathematical modeling are addressed. Then, the proposed output control strategy is developed based on the PI control and the TS fuzzy approximation. A controller ensuring the capacitor voltages balancing has been also introduced in this paper. Experimental results using dSPACE (DS1104) and a laboratory prototype of three-level boost converter demonstrate the flexibility of the proposed controller, its reference tracking capability, and its ability to satisfy the performance specification over the whole operating range of the system.